Biofilm Producing Clinical Staphylococcus aureus Isolates Augmented Prevalence of Antibiotic Resistant Cases in Tertiary Care Hospitals of Nepal - Manandhar, Sarita; Singh, Anjana; Varma, Ajit; Pandey, Shanti; Shrivastava, Neeraj (Frontiers in Microbiology, 2018)
Staphylococcus aureus, a notorious human pathogen, is a major cause of both community as wells as healthcare associated infections. It can cause diversity of recalcitrant infections mainly due to the acquisition of resistance to multiple drugs, its diverse range of virulence factors, and ability to produce biofilm in indwelling medical devices. Such biofilm associated chronic infections often lead to increase in morbidity and mortality posing a high socio-economic burden especially in developing countries. Since biofilm formation and antibiotic resistance function dependent on each other, detection of biofilm expression in clinical isolates would be advantageous in treatment decision. In this premise, we attempt to investigate the biofilm formation and its association with antibiotic resistance in clinical isolates from the patients visiting tertiary health care hospitals in Nepal. Bacterial cells isolated from clinical samples identified as S. aureus were examined for the in-vitro biofilm production using both phenotypic and genotypic assays. All the S.aureus isolates were also examined for susceptibility patterns of clinically relevant antibiotics as well as inducible clindamycin resistance using standard microbiological techniques and D-test respectively. Among 161 S.aureus isolates, 131 (81.4%) were methicillin resistant S.aureus (MRSA) and 30 (18.6%) were methicillin sensitive S.aureus (MSSA) strains. Although majority of MRSA strains (69.6%), showed inducible clindamycin resistance, almost all isolates (97% and 94%) were sensitive towards chloramphenicol and tetracycline respectively. Detection of in-vitro production of biofilm revealed the association of biofilm with methicillin as well as inducible clindamycin resistance among the clinical S.aureus isolates.